CAPACITY ESTIMATION FOR WIRELESS SPREAD-SPECTRUM ORTHOGONAL FREQUENCY DIVISION MULTIPLEXING (SS-OFDM) - WAN ZAKARIA, WAN FARAHIYAH (Universiti Teknologi PETRONAS, 2006)
OFDM is a modulation and multiple access technique that has been a centre of attention in these recent years. Since its development for military application in the 1960s, technical implementations of OFDM have appeared in digital audio broadcasting, asymmetric digital subscriber lines (ADSL), high speed definition television terrestrial broadcasting, and other systems. Because of its capabilities, OFDM becomes a potential candidate as a multiple access technique for beyond 3G mobile technology. This project presents a studyon OFDM performance for wireless mobile environment. Spread-spectrum is employed in combination withOFDM. This project paper presents a simulation of spread-spectrum OFDM using MATLAB and capacity estimation of the simulated environment in wireless channel. The results of the simulation are then compared with the theoretical capacity values of available 3G systems.